SNP array and whole genome sequencing data from: Clonal origin and development of high hyperdiploidy in childhood acute lymphoblastic leukemia - Yang, Minjun; Woodward, Eleanor; Moura-Castro, Larissa Helena; van den Bos, Hilda; Gunnarsson, Rebeqa; Arvidsson, Linda Olsson; Castor, Anders; Duployez, Nicolas; Zuna, Jan; Johansson, Bertil; Foijer, Floris; Paulsson, Kajsa (Lund University, 2023)
This dataset includes high hyperdiploid acute lymphoblastic leukemia (ALL) samples with  Affymetrix SNP Array, Illumina BeadArray or whole genome sequencing with the Illumina platform. The raw data files can be made available after applying for access and agreeing to the terms and conditions for use.
Keywords: Genomics; Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik